Rhomboencephalitis Caused by Listeria Monocytogenes - Stephen Workman; Michael Theal (Canadian Journal of Infectious Diseases)
Listerial rhomboencephalitis is a rare, devastating treatable disease. A previously well 72-year-old man presented with a one-week history of fever and headache. Four days before admission he developed right facial numbness and ataxia. Diagnosis and treatment are described, including the relevant clinical, laboratory and radiological findings.